2015
DOI: 10.1111/dgd.12219
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical allocation ofJAK1mRNAduring spermatogonial stem cell division inXenopus laevis

Abstract: During Xenopus spermatogenesis, each primary spermatogonium (PG), the largest single cell in the testis, undergoes mitotic divisions with a concomitant decrease in size to produce smaller differentiating spermatogonia. The spermatogonial stem cells (SSCs) occur in this PG population. Taking advantage of identifiable and isolatable properties of Xenopus SSCs, we examined JAK1 gene expression during the spermatogenesis because there have been reports on the important role of JAK/STAT pathway in regulating the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Thus, JAK2 activation during testicular oxidative stress and triggering apoptosis is considered a protective mechanism to preserve overall testicular function. This further confirms that JAK2 expression is modulated in parallel to the changes in the testis microenvironment in support of maintaining balanced testis homeostasis during adverse pathological conditions such as tIRI [29].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Thus, JAK2 activation during testicular oxidative stress and triggering apoptosis is considered a protective mechanism to preserve overall testicular function. This further confirms that JAK2 expression is modulated in parallel to the changes in the testis microenvironment in support of maintaining balanced testis homeostasis during adverse pathological conditions such as tIRI [29].…”
Section: Discussionsupporting
confidence: 71%
“…During the early developmental stages of the testis, the JAK/STAT pathway is the mediator of key signals produced by the somatic gonad cells that regulate the development of male germ cells [ 28 ]. It was reported that the JAK2 gene expression is respectively altered to correspond to the status of the testis, which links its activity to the homeostasis of the testis [ 29 ]. Furthermore, the survival of germ cells in the presence of reproductive toxins was attributed to the activation of the JAK/STAT pathway [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the active testis of wall lizards and adult testis of mice are highly proliferative, a higher expression of Arih1 in those phases of testis in wall lizards and mice can be justified. In the predicted interactome database, this protein interacts with the JAK1, which is a protein-tyrosine kinase found in human spermatozoa [ 32 ] and helps in germ cell differentiation in Xenopus [ 33 ]. RASSF7 is a ras association domain-containing protein 7, which negatively regulates stress-induced JNK activation [ 34 ].…”
Section: Discussionmentioning
confidence: 99%